Desenvolvimento de código computacional para análise linear estática de vigas retangulares de altura variável pelo método dos elementos finitos - Enokida, Thiago Seiji (2021)
This work aims to present a finite element formulation and a computational code in Python language for elastic-linear analysis of Euler-Bernoulli beams of variable height under different loading and supports conditions. Structural discretization is done using finite elements with two nodes, each one with two degrees of freedom: vertical displacement and nodal rotation. To aproximate the displacements along the element, a polynomial function of third degree is used. To validate the computational code developed, at the end of the work, numerical examples of some structural elements are presented, and the results are compared with those provided by other authors and other softwares. The results shows that the presented formulation and the developed software provide accurate and reliable solutions for the problem in question.